Adaptation to climate in common bean (Phaseolus vulgaris L.): Photothermal flowering responses in the Eastern, Southern and Great Lakes regions of Africa - Qi, A.; Smithson, James Brady; Summerfield, R.J. (1998)
The photothermal flowering responses of 25 diverse genotypes of common bean (Phaseolus vulgaris L.) were examined in 25 African Bean Yield Adaptation Nurseries (AFBYAN) in the Eastern, Southern and Great Lakes regions of Africa during 1988 and 1991. The trials were located at latitudes between 0.6 and 29.3° and at altitudes from 780 to 2200 m asl. In those 13 trials where daily records of maximum and minimum temperature were available, mean pre-flowering temperatures for individual genotypes ranged from 17.9 to 24.6 °C and mean pre-flowering photoperiods varied from 12.7 to 14.7 h d?1. The time from sowing to first flowering (f) for the 25 genotypes varied from 26 to 42 d in the most-inductive regime to as late as 47 to 80 d in the least-inductive circumstances. The stepwise linear regression on daily mean temperature during the pre-flowering period explained most (52–86%) of the variation in the rate of progress from sowing towards flowering of 21 genotypes. In contrast, in four genotypes (GLPx 92, Ikinimba, G 13671 and G 2816) the fitted values of days to flowering using temperature alone were much earlier than the times observed in the two trials at Maseru in Lesotho (the highest latitude and coolest location). These differences may well reflect photoperiodic effects but from the photothermal combinations encountered this could not be confirmed and so remains to be proven. The overall mean absolute difference between the observed and fitted time to flowering was just 2.6 d. The estimated optimum temperatures ranged from 20.4 to 23.3 °C, at which the minimum times taken to flower were between 28 and 44 d. The derived base and ceiling temperatures ranged from 7.1 to 13.2 °C and from 29.1 to 40.2 °C respectively. Not surprisingly, the use of long-term monthly temperatures (for those trials from which daily temperature records were not available) gave poor agreement between predicted and observed flowering times. The significance and implications of these findings are discussed in relation to those from other studies on the photothermal flowering responses in common bean and the breeding and testing of common beans in Africa.